(untitled) (PERcursos Linguísticos, 2022)
The present proposal is based on a cognitive approach (LAKOFF, 1987), which reflects on the cognitive semantic activity of the Sign Language Translator and Interpreter (TILS) in the legal context. From the semantic issues that have as a starting point the process of human categorization, in which cognitive semantics is observed, developed in the integration of human communication capacity in different social contexts. With this, the objective of this article is to dialogue about the Idealized Cognitive Models, which is based on the fact that all meaning depends on a set of stimuli that are the result of an infinity of motivations, whose sources can be the most diverse, that is, they can be those acquired in interaction with society (LAKOFF, 1987; FELTES, 1992). In the TILS task, the development of comprehension from the source text to the target text requires skills for the task of simultaneous interpretation in the face of legal-term-concepts. The results show that the TILS needs to appropriate a specialized linguistic repertoire, for the effect and efficiency of the task of simultaneous interpretation in the legal context. Keywords: Idealized Cognitive Models. Cognitive Linguistics. Simultaneous Interpretation. Legal Context. Pounds/Portuguese.